Effect of Chitosan-assisted Combination of Laparoscope and Hysteroscope on the Levels of IFN-γ and ICAM-1 in Treatment of Infertility Caused by Obstruction of Fallopian Tubes: Levels of IFN-γ and ICAM-1 in Treatment of Infertility - Liao, Changying; Wang, Zuolong; Li, Hongmei; Zhao, Fengrong; Ling, Ling (Cellular and Molecular Biology, 2023)
This experiment was carried out to investigate the effect of combined treatment of tubal obstruction infertility with deacetylated chitosan and two microscopes on the levels of IFN-γ and ICAM-1. In this study, 100 infertile patients with fallopian tube obstruction who were treated in Jiangbei District Hospital of traditional Chinese medicine from January to August 2019 were divided into two groups according to the alternating grouping method, group A (50 cases) received combined surgery, and Group B (50 cases) received combined surgery and chitosan. The curative effect and postoperative pelvic adhesion of the two groups were analyzed, and the levels of IFN-γ, ICAM-1 and IL6(IL-6), laminin (LN), Transforming growth factor beta 1(TGF-β1) and fibronectin (FN) were observed before and after treatment. Results showed that the total effective rate of Group B was higher than that of Group A (92. 00% vs 76. 00%). The incidence of pelvic adhesion was lower in Group A (4. 00% vs 16. 00%) (P < 0.05). The levels of IFN-γ, ICAM-1, IL-6, LN, FN and TGF-β1 in Group B were significantly lower than those in group A (P < 0.05). In conclusion, the treatment of tubal obstruction infertility with combined deacetylated chitosan and biendoscopy is effective, which can reduce the levels of IFN-γ and ICAM-1, improve the expression of adhesion-related factors and reduce the occurrence of pelvic adhesion.